2023
DOI: 10.1007/s00204-023-03523-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bisphenol F, bisphenol S, and bisphenol AF on cultured human osteoblasts

Abstract: Bisphenol A (BPA) analogs, like BPA, could have adverse effects on human health including bone health. The aim was to determine the effect of BPF, BPS and BPAF on the growth and differentiation of cultured human osteoblasts. Osteoblasts primary culture from bone chips harvested during routine dental work and treated with BPF, BPS, or BPAF for 24 h at doses of 10–5, 10–6, and 10–7 M. Next, cell proliferation was studied, apoptosis induction, and alkaline phosphatase (ALP) activity. In addition, mineralization w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 45 publications
0
1
1
Order By: Relevance
“…Prolonged exposure (21d) to bisphenols in an osteogenic medium inhibited the calcium module formation in the SaOS-2 cells observed in our study, indicating its adverse effects on mineralization processes. Many studies have reported decreased mineralization due to bisphenol exposure in different cells, such as MG-63 (Maduranga Karunarathne et al, 2022), MC3T3-E1 (Hwang et al, 2013), primary human osteoblast (García-Recio et al, 2022;García-Recio et al, 2023). The potential discrepancies between in vitro (calcium nodule formation) and in-vivo mineralization observed in our study could be due to the involvement of system's biological response, including hormonal regulation, rather than the cell culture system.…”
contrasting
confidence: 63%
“…Prolonged exposure (21d) to bisphenols in an osteogenic medium inhibited the calcium module formation in the SaOS-2 cells observed in our study, indicating its adverse effects on mineralization processes. Many studies have reported decreased mineralization due to bisphenol exposure in different cells, such as MG-63 (Maduranga Karunarathne et al, 2022), MC3T3-E1 (Hwang et al, 2013), primary human osteoblast (García-Recio et al, 2022;García-Recio et al, 2023). The potential discrepancies between in vitro (calcium nodule formation) and in-vivo mineralization observed in our study could be due to the involvement of system's biological response, including hormonal regulation, rather than the cell culture system.…”
contrasting
confidence: 63%
“…Similarly, cell proliferation showed significant dose-dependency inhibition in human osteoblast tissues exposed to BPF or BPS [80]. Osteoblasts are specialized cells responsible for bone formation and are crucial in maintaining bone health and integrity.…”
Section: Effects On Bone Developmentmentioning
confidence: 99%